1977
DOI: 10.3323/jcorr1974.26.6_297
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Quantitative Evaluation of Steric Effect on Corrosion Inhibition Efficiency of Branched Alkyl Amines

Abstract: Steric effects of branched alkyl chains on the inhibition efficiency of amine inhibitors for the acid corrosion of iron were studied. Corrosion rates were determined on a pure iron electrode in 6.1M HCl solutions with and without the inhibitors at 30C by polarization measurements. The inhibitors adopted were monoalkyl amines (I), N-ethyl alkyl amines (II), and N dimethyl alkyl amines (III), of which alkyl groups are branched and unbranched chains. The inhibition efficiency of I and II decreased with an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In general, the key to determining the MW of LCOs synthesized by step-growth polymerization is the stoichiometric imbalance between the LC monomer and chain extender [36,40,41]. However, although the amine chain extenders examined in this study were primary amines, they showed different reactivities toward the diacrylate groups in the LC monomer during the aza-Michael addition reaction (i.e., n-butyl > isobutyl > sec-butyl), which is possibly because of the difference in steric hindrance [42]. Considering the different reactivities, the stoichiometry of LC monomer to chain extender was carefully adjusted to be 1.81:1 for LCE-N1, 1.33:1 for LCE-N2, 1.47:1 for LCE-I1, 1.03:1 for LCE-I2, and 1.01:1 for LCE-S1.…”
Section: Molecular Characterizationmentioning
confidence: 91%
See 1 more Smart Citation
“…In general, the key to determining the MW of LCOs synthesized by step-growth polymerization is the stoichiometric imbalance between the LC monomer and chain extender [36,40,41]. However, although the amine chain extenders examined in this study were primary amines, they showed different reactivities toward the diacrylate groups in the LC monomer during the aza-Michael addition reaction (i.e., n-butyl > isobutyl > sec-butyl), which is possibly because of the difference in steric hindrance [42]. Considering the different reactivities, the stoichiometry of LC monomer to chain extender was carefully adjusted to be 1.81:1 for LCE-N1, 1.33:1 for LCE-N2, 1.47:1 for LCE-I1, 1.03:1 for LCE-I2, and 1.01:1 for LCE-S1.…”
Section: Molecular Characterizationmentioning
confidence: 91%
“…Hereafter, we refer to the LCEs prepared with n-BA as LCE-N1 or LCE-N2, with iso-BA as LCE-I1 or LCE-I2, and with sec-BA as LCE-S1, where 1 and 2 represent high and low crosslink density of the LCE, respectively. butyl), which is possibly because of the difference in steric hindrance [42]. Considering the different reactivities, the stoichiometry of LC monomer to chain extender was carefully adjusted to be 1.81:1 for LCE-N1, 1.33:1 for LCE-N2, 1.47:1 for LCE-I1, 1.03:1 for LCE-I2, and 1.01:1 for LCE-S1.…”
Section: Synthesis Of Lcesmentioning
confidence: 99%